Digoxin toxicity with therapeutic serum digoxin concentrations - J. Graafsma; N. Cimic; M. Dijkman; F.M.J. Gresnigt; D. Mitrovic; C. Smit (Toxicology Reports)
Introduction: Digoxin is a cardiac glycoside used for rate control in atrial fibrillation and heart failure. Despite its efficacy, digoxin has a narrow therapeutic window and can cause severe side effects, including life-threatening arrhythmias. Literature and guidelines on management of digoxin toxicity remain inconsistent whether to include serum digoxin concentrations as a key criterium for diagnosing digoxin toxicity and determining the indication for digoxin-specific antibody fragments. This report presents a case of digoxin toxicity at therapeutic serum concentrations. Case report: A 76-year-old male presented with bradycardia, hyperkalemia, and acute kidney injury following gastrointestinal bleeding. Despite serum digoxin concentrations within the therapeutic range (1.4 ng/ml), the patient exhibited symptoms consistent with severe digoxin toxicity. Initial treatments, including calcium gluconate, insulin-glucose, and sodium bicarbonate, failed to resolve hyperkalemia and/or bradycardia. Administration of 40 mg digoxin-specific antibody fragments led to rapid normalization of potassium levels, improved heart rate, and hemodynamic stabilization, indicative for severe digoxin toxicity despite therapeutic serum concentrations. Discussion: This case demonstrates that digoxin toxicity can occur at serum concentrations in therapeutic range, emphasizing the importance of clinical features in diagnosing digoxin toxicity. Current guidelines vary on the role of serum digoxin concentrations in guiding the use of digoxin-specific antibody fragments, but this case underscores its efficacy in resolving symptoms related to digoxin toxicity, even at low serum concentrations.